Function of HAb18G/CD147 in Invasion of Host Cells by Severe Acute Respiratory Syndrome Coronavirus - Chen, Zhinan; Mi, Li; Xu, Jing; Yu, Jiyun; Wang, Xianhui; Jiang, Jianli; Xing, Jinliang; Shang, Peng; Qian, Airong; Li, Yu; Shaw, Peter X.; Wang, Jianwei; et al. (The Journal of infectious diseases, 2005)
To identify the function of HAb18G/CD147 in invasion of host cells by severe acute respiratory syndrome (SARS) coronavirus (CoV), we analyzed the protein-protein interaction among HAb18G/CD147, cyclophilin A (CyPA), and SARS-CoV structural proteins by coimmunoprecipitation and surface plasmon resonance analysis. Although none of the SARS-CoV proteins was found to be directly bound to HAb18G/CD147, the nucleocapsid (N) protein of SARS-CoV was bound to CyPA, which interacted with HAb18G/CD147. Further research showed that HAb18G/CD147, a transmembrane molecule, was highly expressed on 293 cells and that CyPA was integrated with SARS-CoV. HAb18G/CD147–antagonistic peptide (AP)–9, an AP of HAb18G/CD147, had a high rate of binding to 293 cells and an inhibitory effect on SARS-CoV. These results show that HAb18G/CD147, mediated by CyPA bound to SARS-CoV N protein, plays a functional role in facilitating invasion of host cells by SARS-CoV. Our findings provide some evidence for the cytologic mechanism of invasion by SARS-CoV and provide a molecular basis for screening anti-SARS drugs